Integrative systemic and family therapy for social anxiety disorder: Manual and practice in a pilot randomized controlled trial (SOPHO-CBT/ST) - Hunger-Schoppe, Christina; Schweitzer, Jochen; Hilzinger, Rebecca; Krempel, Laura; Deußer, Laura; Sander, Anja; Bents, Hinrich; Mander, Johannes; Lieb, Hans (Frontiers in Psychology, 2022)
Social anxiety disorders (SAD) are among the most prevalent mental disorders (lifetime prevalence: 7 to 12%), with high impact on the life of an affected social system. We developed a manualized disorder-specific integrative systemic and family therapy (ISFT) for SAD, evaluated for its feasibility in a pilot randomized controlled trial (RCT). The ISFT is inspired by Helm Stierlin’s concept of related individuation during the early 1980s, which has since continued to be refined. It integrates solution-focused language, social network diagnostics and genogram work, and resource- as well as problem-orientation for case conceptualization and therapy planning. Post-Milan symptom prescription to fluidize the presented symptoms is at the heart of the ISFT. Theoretically, the IFST grounds in radical constructivism and “Cybern-Ethics”, multi-directional partiality and a both/and attitude towards a disorder-specific versus non-disorder-specific therapy approach. SAD is understood from the viewpoint of social systems theory, especially in adaptation to a socio-psycho-biological explanatory model of social anxiety. In a prospective multicenter, assessor-blind pilot RCT (Hunger et al., 2020), we included 38 clients with SAD (ICD F40.1; Liebowitz Social Anxiety Scale, LSAS-SR > 30): 18 patients participated in the ISFT, and 20 patients in Cognitive Behavioral Therapy (CBT) (age: M = 36 years, SD = 14). Within-group, simple-effect intention-to-treat analyses showed significant reduction in social anxiety (LSAS-SR; ISFT: d = 1.67; CBT: d = 1.04), while intention-to-treat mixed-design ANOVA demonstrated the advantage of ISFT (d = 0.81). Per-protocol analyses supported these results. The remission rate based on blind diagnosticians’ ratings was good to satisfactory (Structured Clinical Interview, SCID; 78% in ST, 45% in CBT, p = .083); this has yet to be verified in a subsequent confirmatory RCT. The article will present the ISFT rationale and manual, including a special focus on multi-person settings, and the central findings from our pilot RCT (Hunger et al., 2020).